Temperature insensitive broad and flat gain C-band EDFA based on macro-bending - Hajireza, Parsin; Emami, Siamak Dawazdah; Abbasizargaleh, Soroush; Harun, Sulaiman Wadi; Kumar, Deepak; Abdul-Rashid, Hairul Azhar (Electromagnetics Academy, 2010)
In this paper, a new method is proposed to achieve a temperature insensitive, broad and flat gain C-band erbium-doped fiber amplifier (EDFA) with aid of macro-bending. This gain flattened C-band EDFA is demonstrated by utilizing 2.5 m macro-bent Erbium-doped fiber (EDF) at room temperature of 25°C. Further to this, it is shown that gain fluctuation at different temperatures is compensated in the proposed design. The EDFA performance at different temperatures is investigated for various macro-bending diameter and EDF length. The gain saturation and energy transfer from shorter wavelengths to longer wavelengths can be controlled by varying the bending radius and the length of the doped fiber, consequently, a flattened and broadened gain profile in the C-band region can be achieved. The amplifier uses a 2.5m long EDF with 2000 ppm concentration and bending radius of 6.5mm as a gain medium. The gain variation of the EDFA is obtained within ±0:5 dB over 35nm bandwidth of C-band region.